2010
DOI: 10.1002/hep.23250
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tumor Necrosis Factor α–Converting Enzyme Activity Induces Insulin Resistance and Hepatosteatosis in Mice

Abstract: Tumor necrosis factor ␣-converting enzyme (TACE, also known as ADAM17) was recently involved in the pathogenesis of insulin resistance. We observed that TACE activity was significantly higher in livers of mice fed a high-fat diet (HFD) for 1 month, and this activity was increased in liver > white adipose tissue > muscle after 5 months compared with chow control. In mouse hepatocytes, C 2 C 12 myocytes, and 3T3F442A adipocytes, TACE activity was triggered by palmitic acid, lipolysaccharide, high glucose, and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
78
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 32 publications
2
78
0
Order By: Relevance
“…sortilin reduction to be mediated at least partially through the post-translational modification (shedding) involving TACE activity (25), which could be activated by a PKC activator, TPA (26). Intriguingly, several recent studies have demonstrated that TACE activity is increased in the skeletal muscles of obese type 2 diabetes patients and in lipid-induced insulin resistance (43,44). In addition, increased TACE activity has been directly implicated in the pathogenesis of insulin resistance, which is generally explained by the augmented secretion of TNF-␣ (43,45,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sortilin reduction to be mediated at least partially through the post-translational modification (shedding) involving TACE activity (25), which could be activated by a PKC activator, TPA (26). Intriguingly, several recent studies have demonstrated that TACE activity is increased in the skeletal muscles of obese type 2 diabetes patients and in lipid-induced insulin resistance (43,44). In addition, increased TACE activity has been directly implicated in the pathogenesis of insulin resistance, which is generally explained by the augmented secretion of TNF-␣ (43,45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, several recent studies have demonstrated that TACE activity is increased in the skeletal muscles of obese type 2 diabetes patients and in lipid-induced insulin resistance (43,44). In addition, increased TACE activity has been directly implicated in the pathogenesis of insulin resistance, which is generally explained by the augmented secretion of TNF-␣ (43,45,46). Thus, our findings provide an important connection between TACE activity and PKC-dependent sortilin reduction in skeletal muscle cells under palmitate-induced insulinresistant conditions, which appeared to be directly involved in the pathogenesis of impaired GLUT4 trafficking as discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that TACE activity was significantly higher in mice fed with high fat diet (HFD) compared with chow controls (Fiorentino et al, 2010). In addition, TACE heterozygously knockout mice were protected against HFD-induced obesity (Serino et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TACE heterozygously knockout mice were protected against HFD-induced obesity (Serino et al, 2007). Furthermore, mice that lack tissue inhibitor of metalloproteinase 3, an endogenous inhibitor of ADAM families, showed an accelerated development of complications of obesity under HFD regimen (Menghini et al, 2009;Fiorentino et al, 2010). The collective findings suggested that TACE could be a possible therapeutic target of obesity-related diseases (Menghini et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…9, 10 Although neither TNF-α-nor TNF-α receptor-deficient mice show significant changes Tace Inactivation Ameliorates Insulin Resistance in body weight (BW) when fed a HFD, mice lacking functional Tace exhibit a lean phenotype and markedly increased energy expenditure, suggesting an important role of Tace in energy homeostasis. 11 To evaluate the pathogenic role of Tace in obesity-induced metabolic disorders, we generated Tace flox/flox /Mx1-Cre mice (TaceMx1) to allow temporal systemic deletion of Tace as previously reported, 12 because Tace-deficient mice die perinatally.…”
mentioning
confidence: 99%